EVALUATION OF STRUCTURAL CHANGES IN BALLERINA'S FEET FROM MANAUS (Fiep Bulletin - online, 2011)
The objective of this research was to examine the anthropometric characteristics and the longitudinal arch on the feet of ballerinas in the city of Manaus, realizing the most affected and most recurrent changes on the structures of this body part. The research sample consisted of 10 female ballerinas aged between 18 and 25 years old. To collect the data we used calipers and pedigraph. It was possible to see that the variables length of the foot, heel-toe length I and width of the metatarsal heads of the subjects of this study population, when compared to Brazilian women showed mean similar changes of the plantar arch, and presence of pathologies such as hallux valgus were also observed. Through this research, it was observed that the prolonged practice of classical dance, can cause changes in foot anthropometry of its practitioners due to external forces such as body segment is exposed in this technique. These changes become more present and more frequently when the classical dance is performed since childhood, a phase in which the musculoskeletal structures are still modeling and fitness activities and forces both internal and external are exercised over them.
Keywords: biomechanics; anthropometry; dancers